rasterstack4cov - Mills, L. Scott; Bragina, Eugenia V.; Kumar, Alexander V.; Zimova, Marketa; Lafferty, Diana J.R.; Feltner, Jennifer; Davis, Brandon M.; Hacklander, Klaus; Alves, Paulo C.; Good, Jeffrey M.; Melo-Ferreira, Jose; Dietz, Andreas; et al. (Dryad Digital Repository, 2018)
This is the a raster stack of the three covariates (bio_2, bio_3 & snow) used in making the winter white probability maps. It is needed to run the R script.